Biventricular mechanical pattern of the athlete"s heart: comprehensive characterization using 3D echocardiography. (4th February 2022) - Fabian, A; Ujvari, A; Tokodi, M; Lakatos, BK; Eles, Z; Kiss, O; Babity, M; Sydo, N; Csulak, E; Vago, H; Szabo, L; Kiss, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Regular, intense exercise results in complex morphological and functional cardiac remodeling, commonly referred to as the athlete"s heart. While left ventricular (LV) adaptation is thoroughly studied, data are scarce concerning the right ventricular (RV) mechanical changes and their continuum with exercise performance. Accordingly, our aim was to characterize biventricular morphology and function and its relation to sex, age and sport classes in a large cohort of elite athletes using 3D echocardiography. Four hundred and twenty-two elite, competitive athletes (male/female: 295/127, adult/adolescent: 207/215) from the 4 major sport classes (mixed type n = 293; endurance n = 88; power n = 33; skill n = 8) and healthy, sedentary volunteers (n = 55) were enrolled. 3D transthoracic echocardiographic datasets were acquired to quantify LV and RV end-diastolic volumes (EDVi), and ejection fractions (EF). In order to characterize biventricular mechanical parameters, LV and RV global longitudinal (GLS) and global circumferential strains (GCS) were measured using dedicated softwares. Additionally, all subjects underwent cardiopulmonary exercise testing in order to determine peak oxygen uptake (VO2/kg). Athletes had significantly higher LV and RV EDVi compared with controls, whereas male athletes had larger volumes than female athletes, and adult athletes had also larger LV EDVi than adolescent athletes (all p < 0.05). However, RV EDVi was similar between the two age groups. Endurance athletes had significantly larger RV EDVi compared with the other sport classes (ANOVA p < 0.05).  Concerning biventricular functional parameters, athletes had significantly lower resting LV and RV EF (athletes vs. controls; LVEF: 57 ± 4 vs. 61 ± 5%; RVEF: 55 ± 5 vs. 59 ± 5%; p < 0.001) as well as LV GLS (-19.2 ± 2.3 vs. -21.2 ± 2.0%), LV GCS (-27.7 ± 3.0 vs. -31.0 ± 3.5%), and RV GCS (-20.9 ± 4.4 vs. -24.5 ± 4.5%; all p < 0.001) compared with controls. In contrast, RV GLS (-21.8 ± 3.4 vs. -22.2 ± 3.6%) did not differ between athletes and controls. The exercise-induced relative decrease in LV GLS (9.5 ± 10.7%) and LV GCS (10.7 ± 9.8%) was similar, however, the decrement in RV GCS (14.8 ± 17.8%) was disproportionately larger compared with RV GLS (1.7 ± 15.4%, p < 0.01) in the athlete population. By multivariable linear regression analysis among echocardiographic parameters using ordinary least squares, RVEDVi was found to be the strongest and independent predictor of VO2/kg, followed by RV GCS and LV EDVi. Regular physical exercise results in significant and specific changes in LV and RV geometry and function. Resting LV mechanics of the athlete"s heart is characterized by a balanced decrement in GLS and GCS, however, in the RV the circumferential shortening decreases disproportionately compared with the longitudinal shortening. Moreover, this mechanical pattern is associated with better exercise capacity, which emphasizes the importance of the RV in determining athletic performance.